Android open conference 2011 : complete video compilation. (O'Reilly Media, 2011)
"This video compilation includes every session of the October 2011 inaugural of O'Reilly's Android Open - the first conference to cover the entire Android ecosystem. A crowd of developers, IT pros, business leaders, and marketers showed up at this hugely successful meet and greet to share best practices, tools, models, and lessons learned. If you're in business to create, sell, or market products in the Android space, if you're launching an Android-centric venture or need to take stock of the competitive landscape, this video series is a must."--Resource description page.